2019
DOI: 10.1038/s41401-019-0231-y
|View full text |Cite|
|
Sign up to set email alerts
|

Integrating yeast chemical genomics and mammalian cell pathway analysis

Abstract: Chemical genomics has been applied extensively to evaluate small molecules that modulate biological processes in Saccharomyces cerevisiae. Here, we use yeast as a surrogate system for studying compounds that are active against metazoan targets. Large-scale chemical-genetic profiling of thousands of synthetic and natural compounds from the Chinese National Compound Library identified those with high-confidence bioprocess target predictions. To discover compounds that have the potential to function like therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In addition, mitochondrial proliferation is increased, indicating that also in this unicellular eukaryote, mitochondrial metabolism and functionality may contribute to the induction and/or maintenance of the senescent state [ 135 ]. Although both yeast and C. elegans lack complex traits associated with senescence, these models contributed substantially to our current understanding of fundamental molecular aspects associated with aging and senescence [ 11 , 12 , 15 , 132 ]. Genes identified in such screens were subsequently validated in higher eukaryotic model systems, such as human cultured cells [ 55 , 136 , 137 ], organoids [ 138 , 139 ], and mice [ 140 , 141 ], and promoted the identification of promising molecules for translational approaches [ 55 ].…”
Section: Identification Of Dietary and Pharmacological Interventions Modulating Cellular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mitochondrial proliferation is increased, indicating that also in this unicellular eukaryote, mitochondrial metabolism and functionality may contribute to the induction and/or maintenance of the senescent state [ 135 ]. Although both yeast and C. elegans lack complex traits associated with senescence, these models contributed substantially to our current understanding of fundamental molecular aspects associated with aging and senescence [ 11 , 12 , 15 , 132 ]. Genes identified in such screens were subsequently validated in higher eukaryotic model systems, such as human cultured cells [ 55 , 136 , 137 ], organoids [ 138 , 139 ], and mice [ 140 , 141 ], and promoted the identification of promising molecules for translational approaches [ 55 ].…”
Section: Identification Of Dietary and Pharmacological Interventions Modulating Cellular Senescencementioning
confidence: 99%
“…that contribute to induction and maintenance of the senescent state are conserved in evolution. Thus, simple and easy‐to‐manipulate model organisms such as the yeast Saccharomyces cerevisiae ( S. cerevisiae ) or the nematode Caenorhabditis elegans ( C. elegans ) are frequently used to elucidate fundamental aspects of cell damage and disruption of homeostasis, which promote senescence in vertebrates [ 10 , 11 , 12 , 13 , 14 , 15 ]. However, there is little evidence for senescence in these simple models, which are evolutionarily quite distant from humans.…”
Section: Introductionmentioning
confidence: 99%
“…For perspective, ATP7A is an important copper transporter that regulates the absorption of copper in the intestinal tract [70]. Yeast cells are considered an ideal model for the genetic analysis of mammalian genomes [71,72]. Interestingly, a report by Sowada et al [73] showed increased copper sensitivity of yeast cells lacking VPS35.…”
Section: Discussionmentioning
confidence: 99%